SNP discovery for genetic diversity and population structure analysis coupled with restriction-associated DNA (RAD) sequencing in walnut cultivars of Sichuan Province, China. Issue 1 (1st January 2020) - Wang, Jing-Yan; Yan, Si-Yu; Hui, Wen-Kai; Gong, Wei
Abstract: The walnut is an excellent food product with abundant nutrients. However, the inference of its population structure has been hindered by the intricate phylogenetic relationships among Juglans species. In this study, RAD sequencing was conducted to investigate the genetic variation and population structure among 41 walnut cultivars from Southwestern Sichuan (SS, n  = 10), Eastern Sichuan (ES, n  = 26) and Northern China (NC, n  = 5). The resulting 6357 single-nucleotide polymorphisms divided the 41 walnut cultivars into two major groups corresponding to the ES and SS gene pools, and NC was clustered with the ES1 subgroup. Additionally, two cultivars, WB01 and SMJ, were reclassified to correct their previous morphological classifications. The migration rate from ES to SS was greater than that in the reverse direction, and the genetic differentiation between the ES and SS populations was high. Moreover, the estimated expected heterozygosity ( He = 0.308) and polymorphism levels ( Pi ( π ) = 0.030) of the SS group were greater than those of the ES group. Similarly, the average genetic distance of the SS population (0.563) was higher than that of the ES population (0.522), and the rate of linkage disequilibrium decay in the SS population was faster. All the results indicate that the SS population has greater genetic diversity and is more primitive than the ES group. The present study provides a theoretical basis for the division, conservation, and utilization of walnut germplasm resources, and these findings can be applied in breeding programs to obtain high-quality cultivars of Juglans .